Male rock lizards may compensate reproductive costs of an immune challenge affecting sexual signals. (20th May 2020) - Rodríguez-Ruiz, Gonzalo; Ortega, Jesús; Cuervo, José Javier; López, Pilar; Salvador, Alfredo; Martín, José
Abstract: Sexual signals can be evolutionarily stable if they are condition dependent or costly to the signaler. One of these costs may be the trade-off between maintaining the immune system and the elaboration of ornaments. Experimental immune challenges in captivity show a reduction in the expression of sexual signals, but it is not clear whether these detrimental effects are important in nature and, more importantly, whether they have reproductive consequences. We designed a field experiment to challenge the immune system of wild male Carpetan rock lizards, Iberolacerta cyreni, with a bacterial antigen (lipopolysaccharide). The immune challenge decreased relative reflectance of ultraviolet structural and melanin-dependent sexual coloration in the throat and the lateral ocelli, whereas the carotenoid-dependent dorsal green coloration was not affected. Immune activation also decreased proportions of ergosterol and cholesta-5, 7-dien-3-ol in femoral secretions. These results support a trade-off between the immune system and both visual and chemical sexual ornaments. Moreover, the reproductive success of males, estimated with DNA microsatellites, depended on the expression of some color and chemical traits. However, the immune challenge did not cause overall differences in reproductive success, although it increased with body size/age in control but not in challenged males. This suggests the use of alternative reproductive strategies (e.g., forced matings) in challenged males, particularly in smaller ones. These males might consider that their survival probabilities are low and increase reproductive effort as a form of terminal investment in spite of their "low-quality" sexual signals and potential survival costs. Abstract : It is not just a matter of beauty. Sick male lizards are unable to pay the cost of being attractive to females and can only produce low-quality sexual ornaments. Only the best healthy males are able to produce expensive sexual ornaments, like colorful patches and attractive scents, which females prefer. However, despite the low attractiveness of sick males, alternative mating strategies may allow them to fertilize some females and to sire as many offspring as attractive males.